Rudyard Kipling: A study in the pattern of critical comment on Rudyard Kipling among the periodical reviewers during the period from 1890 to 1900. - Buckley, Edward J. (University of Ottawa (Canada), 1958)
This thesis has attempted to discover the pattern of periodical critical comment on Rudyard Kipling and his work during the period 1890 to 1900. This period was Kipling's most productive and the one during which his reputation was made. During this time his works and ideals were seriously considered from many points of view. His explosive arrival upon the London scene caught the reviewers napping and he succeeded in obtaining public applause before the critics were really aware of his presence. Their feeble attempts to appraise his works during the first year did little more than re-echo the popular applause. However, they found his short stories to be a strange medium and so they called for a long novel. This Kipling provided in The Light That Failed and the critics truly dissected it and declated Kipling to be a poor writer; failing to see life as a whole he focused the spot light on isolated facts. As a result of the novel's failure some critics felt that both his arrival and his works were the sensation of a moment and would soon pass away. In fact the next collection of verse failed to raise his standard any higher and his year of silence in 1893 seemed to indicate the truth of the prediction that the possible "Anglo-Indian Dickens" had slid from view. The publication of The Jungle Books saw a rapid return of public interest. His studies of animal life won him a comparison with Aesop and aroused the interest of the deeper critics who were starting to find an association between his tales and his philosophy. The works which followed The Jungle Books strengthened his position as a writer of Empire and an exponent of Imperial ideals. The Seven Seas and The Day's Work seemed to present a relationship between his "Jungle" ideas and his "Imperial" ideals. The whole trend was highlighted by the publication in July, 1897 of Recessional , a short poem which received more attention than any other item he created. In fact the year 1899 was taken up with reviewers' attempts to evaluate and tie together Kipling's philosophical notions relative to men, to work and to empire. That there were definite patterns in the critical comment is evident. It rose steadily, except for two periods of lull, from surprise at his arrival to an attempted interpretation of his philosophy. Within the ten year period his techniques, and story content were well explored, and from his works the critics had drawn his ideals of empire, its place in the lives of men and men's place in the concept of empire.
Keywords: Literature, English.